Kesenian Kubrosiswo, Wahana Dakwah Petani Pedesaan Jawa - Agus Maladi Irianto (Program Studi Sastra Indonesia, Fakultas Ilmu Budaya, Universitas Diponegoro, 2017)
A farmer community in Javanese village, has developed art as an integrative need and, functionally, relates it to the culture in the area where they were living since long time ago. One of performing art has by a Javanese village farmer community that is still preserved till recently is Kubrosiswo. Kubrosiswo, is considered as one of the connector of ritual values with the concepts of simplicity and mutual cooperation between people in one farmer community.Kubrosiswo performing art is also identified as asocial activity namely slametan that is regularly done by Javanese farmers. The Javanese farmer community believes that slametan is able to accommodate social and ritual demand.